2009
DOI: 10.1159/000213486
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Occurrence of Inflammatory Bowel Disease and Myelodysplastic Syndrome due to Chromosomal Abnormalities in Bone Marrow Cells

Abstract: Background/Aims: Although chromosomal abnormalities in bone marrow (BM) cells, such as trisomy 8, are risk factors for the development of inflammatory bowel diseases (IBD) as well as myelodysplastic syndrome (MDS), the mechanisms of how these cytogenetic abnormalities cause intestinal inflammation are poorly understood. Methods and Results: A 55-year-old man with a 3-month history of watery diarrhea, fever and abdominal pain was admitted. Blood examinations revealed pancytopenia. Pathological analysis and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…It is well known that trisomy 8 is a common chromosomal abnormality in MDS. It often manifests as GI lesions, including small bowel lesions [8]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well known that trisomy 8 is a common chromosomal abnormality in MDS. It often manifests as GI lesions, including small bowel lesions [8]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in this case, many patients diagnosed with IBD frequently presented with clinical manifestations of MDS before diagnosis. 57 Other acute and chronic autoimmune disorders associated with MDS are diverse types of vasculitis, autoimmune anemias, several rheumatic and skin disorders and certain thyroid diseases. 3,8,9 …”
Section: The Inflammatory and Autoimmune Nature Of Mdsmentioning
confidence: 99%
“…14,15 Indeed, patients frequently present with clinical manifestations of MDS before diagnosis of IBD. 57 This has led to the speculation that MDS and IBD could have a common pathogenesis. For instance, one case study reported that the same abnormal BM karyotype is associated with the development of both MDS and IBD.…”
Section: The Inflammatory and Autoimmune Nature Of Mdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, BM cells from this patient had double chromosomal abnormalities: trisomy 8 and der(1;7)(q10;p10). Monocytes from this patient acquired inflammatory phenotypes, because the presence of these chromosomal abnormalities in BM cells allowed the development of colitogenic monocytes, which exhibited the resistance to apoptosis and produced pro‐inflammatory cytokines upon stimulation with TLR ligands . These findings suggest that the MDS‐associated chromosomal abnormalities of trisomy 8 and der(1;7)(q10;p10) may lead to the development of unexpected clinical manifestations.…”
mentioning
confidence: 78%